Konsep Pembentukan Islamic Branding Tinjauan Etika Bisnis Islam - Isnaini, Nur (Universitas Negeri Surabaya, 2022)
Formation of a name with Islamic religious elements, namely with the term Islamic Branding, namely using Islamic labels as a product identity both in terms of names that lead to Islamic elements in the form of halal labels in order to get Muslim consumers in marketing. Therefore, the context of this problem refers to how Islamic ethics should be applied in the formation of Islamic branding, and how Islam provides boundaries in Islamic branding ethics. While the purpose of this study is regarding the concept of establishing Islamic branding in accordance with Islamic business ethics. This research method uses library research techniques (library research). While the results of this study the application of Islamic branding in Islamic business ethics are: 1. Positive image: a) build loyalty, b) avoid unhealthy competition. 2. Islamic products: a) products must be halal and beneficial, b) product quality must be guaranteed. 3. Fair pricing: a) fair profit taking, b) keeping unfair prices at bay. 4. Islamic Marks: a) avoid trademark disputes, b) halal labels must be guaranteed. 5. Islamic promotion: a) use of spokespersons according to ethics, b) use of reliable slogans.